Increased plasma leptin as a novel predictor for psychopathological depressive symptoms in chronic schizophrenia - Jinjie Xu; Yumei Jiao; Mengjuan Xing; Yezhe Lin; Yousong Su; Wenhua Ding; Cuizhen Zhu; Yanmin Peng; Dake Qi; Donghong Cui (General Psychiatry)
Background Depressive symptoms are often seen in schizophrenia. The overlap in presentation makes it difficult to distinguish depressive symptoms from the negative symptoms of schizophrenia. The adipokine leptin was found to be altered in both depression and schizophrenia. There are few studies focusing on the prediction of leptin in diagnosis and evaluation of depressive symptoms in schizophrenia.ObjectiveAims To assess the plasma leptin level in patients with schizophrenia and its relationships with depressive symptoms.Methods Cross-sectional studies were applied to (1) compare the levels of plasma leptin between schizophrenia (n=74) and healthy controls (n=50); and (2) investigate the relationship between plasma leptin levels and depressive subscores.Results (1) Plasma leptin levels were significantly higher in patients with schizophrenia than in healthy controls. (2) Correlation analysis revealed a significant negative association between leptin levels and the depressed factor scores on the Positive and Negative Syndrome Scale (PANSS). (3) Stepwise multiple regression analyses identified leptin as an influencing factor for depressed factor score on PANSS.Conclusion Leptin may serve as a predictor for the depressive symptoms of chronic schizophrenia.